EVALUASI PELAKSANAAN PERDA NOMOR 3 TAHUN 2002 TENTANG HIBURAN UMUM KOTA PEKANBARU (HIBURAN KARAOKE DI KOTA PEKANBARU) - Zulmey Akhirisya; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Local regulation implementation No. 3 Year 2002 concerning Pekanbaru City publik entertaiment towards the karaoke venues that is not following the local regulation and causing violations that occors. The venues are allowed to operate from 8 a.m. unti 10 p.m. at night. But in fact, these karaoke venies are operating until dawn. Operation requirement and permits are also have been violated. Karaoke venues that is being located nearby the house of worship and disturb the tranquility of residences is the other kind of violations that happens. Most karaoke venues serve liquors and also functionalized for drug user and a prostitution’s facilities. This conclude that the local regulation that has been approved doesn’t function as effectively, effetively and has failed to achieve the goals that has been given. The objective of this research is to evaluate and discover certain factors that are effecting the evaluation of local regulation implementation No. 3 Year 2002 concerning Pekanbaru City publik entertaiment towards the karaoke venues itself. Researcher use William N Dunn’s theory that explain the criteria of an evaluation of a policy includes effectivity, efficiency, sufficiency, responsivity and regularity. This research used qualitative descriptive methods, data collecting technic througt observation and interview where the stakeholders in this case are considered as an informant. The outcome of this research shows that the evaluation of local regulation implementation No. 3 Year 2002 concerning Pekanbaru City publik entertaiment towords the karaoke venues has not been implemented very well. This is causing this regulation is becoming very ineffective. The ineffective of the regulation is becoming the cause of this situation. The equlizzation of these public entertaiment venues operational hour has not been evaluted properly and causing the regularity of the regulation implementation No. 3 Year 2002 concerning Pekanbaru City public entertaiment has not been applied thoroughly. This situation is also causing the regulation has lack of responsivity from stakeholders towards this local regulation. The factors that is effecting the local regulation implementation No. 3 Year 2002 concerning Pekanbaru City public entertaiment towards the karaoke venues is human resources and time limitation.Keyword : Evaluations, Local Regulations and Karaoke